Correlation Between Blood Pressure, Hemoglobin Content and Intellectual Status of the School Going Children (10-12 Years) in Agartala, India and Effect of the Extracts of the Leaves of Asteracantha longifolia Nees - Debnath, Manabendra; De, Biplab (Asian Journal of Chemistry, 2010)
The intellectual status of the school going children (10-12 years) were correlated with the hemoglobin content and blood pressure. A positive correlation was established for both the male and female students irrespective to tribal and non-tribal (Bengali). Further the extract of the leaves of Asteracantha longifolia Nees was subjected to see the impact of supplementation on hemoglobin contents of the blood in mice and found that the extract was the enhancer of hemoglobin content, which may have the efficacy to increase the intellectual status of the children as knowledged from the villagers residing at Tripura, India.